Study the effect of kerosene on some physiological activities in Oscillatoria splendida - Ali Muayad Sultan; Hammed S. Khamees; Ayman A. Saleem (Tikrit Journal of Pure Science)
The effect of different concentration of Kerosene had been examined upon Oscillatoria splendida, The optical density had been depended as measure for growth as well as chlorophyll a concentration, Phycocyanin pigment and protein concentration as an indicator of Kerosene effects, in addition to morphological changes. The optical density of growth in the control sample was (0.34), while it was (0.23) at 0.25% of kerosene concentration, It is noted slowing growth with high concentration of kerosene treatment, at 0.5% peak of growth was (0.08), and resisted the influence of the Kerosene transactions 1% and 2%, but with low growth values. concentration of chlorophyll pigment under effect of 0.25% was (0.32) mg /ml, for as low as (0.165) mg /ml at 0.5% of kerosene, Chlorophyll concentrations have fallen to the minimum under the influence of transactions 1% and 2%. Protein concentration was (0.215, 0.86) mg/ml under the influence of kerosene transactions 0.25% and 0.5% respectively, In spite of the doubling kerosene concentration to 1% and 2%, but the values of the protein did not reduced Completely. Some morphological changes were observed under the effect of kerosene such as yellowing of cells colors with a slight increase in the length of the cells. As well as the absorption spectrum infrared by FTIR show that the Oscillatoria splendida consume many of bundle such as (2870) cm-1 and (2950) cm-1, also the disappearance 2300) cm -1, 1500 cm -1, with the appearance a new bundle at (800) cm-1 Attributed to the introduction of a new compound not found in control sample.